TUMBUHAN BERGUNA PADA MASYARAKAT PERCAMPURAN DI DESA LEMO UTARA KECAMATAN AMPIBABO KABUPATEN PARIGI MOUTONG SULAWESI TENGAH - Mirawati Mirawati; Eny Yuniati (Biocelebes, 2014)
The research which was about useful plant in mixing society at North Lemo village Ampibabo district Parigi Moutong Regency Sulawesi Province had been carried out from February to April 2013. The objective of the research was to find out the types of plants, parts used and the way to use for the society in the research. This was a descriptive research done through semi structured interview. The research results show that Lauje tribe noted 71 types of plant used, whereas buginese noted 58 types of plants used. The plant have the highest value of ICS on Kaili Lauje tribe was ‘pae’ (Oryza sativa L) with ICS value was 95, whereas at buginase have the same value. The mixing society in North Lemo village have very good knowladge in the way to use plants in the daily life, either food plants, medicine, tradition, decoration, spices, building, coloring or the other needs. Keywords: Useful plants, Mixing Society North Lemo Village.